2020
DOI: 10.1108/jcs-07-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

The team as a secure base revisited: remote working and resilience among child and family social workers during COVID-19

Abstract: Purpose Social work teams can provide a secure base for social workers, supporting them to manage the emotional demands of child and family social work (Biggart et al., 2017). As the COVID-19 pandemic has necessitated increased remote working, social workers have needed to maximise their use of virtual networks and navigate new ways of connecting with colleagues. This study aims to examine the extent to which social work teams can function as a secure base in the context of remote working. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 10 publications
3
54
0
4
Order By: Relevance
“…The adoption or enhanced use of technologies was an important means for garnering social support and information for participants in this study. The pandemic has also stimulated transformation in the social work profession -through virtual delivery of services, community engagement and clinical practices (Cook et al 2020). Given the very real issue of social isolation and loneliness for older adults (Wu 2020), and older immigrant adults (Frank 2020) in particular, the use of technology such as social media and video chats might mitigate these concerns (Hajek and König 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The adoption or enhanced use of technologies was an important means for garnering social support and information for participants in this study. The pandemic has also stimulated transformation in the social work profession -through virtual delivery of services, community engagement and clinical practices (Cook et al 2020). Given the very real issue of social isolation and loneliness for older adults (Wu 2020), and older immigrant adults (Frank 2020) in particular, the use of technology such as social media and video chats might mitigate these concerns (Hajek and König 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These data might be unexpected, but they are more understandable if we consider that greater personal recognition is related to responsibility, assumption of duties, involvement in work, etc. In this way, people who showed these qualities in professional practice during COVID-19 have been affected in terms of personal fulfillment by not achieving the expected results in their work activity, an aspect that can lead to demotivation and lack of personal confidence about work performance [ 54 , 55 , 56 , 57 ] and immediate bosses, even reaching irritability, discouragement, and negative feelings about their professional practice [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the easement of lockdown restrictions between July and November 2020 across most of the UK could have influenced workforce pressures and the results, and well-being and WRQoL could have deteriorated between the different surveys. Qualitative findings from Morse and Dell (2021) and Cook et al (2020) found staff finding it difficult to work remotely with a lack of resources, team support and opportunities. Additionally, social work practice during this time was characterised as stressful and overwhelming.…”
Section: Discussionmentioning
confidence: 99%